1993
DOI: 10.2527/1993.714939x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating rate on palatability and associated properties of pre- and postrigor muscle

Abstract: Precooked, uncured meat is not widely available to consumers, partially because of associated palatability problems and lack of published information on heat uptake under different industrial conditions. The objectives of this study were to determine the tenderness, extent of lipid oxidation, and total cooking losses in pre- and posterior beef and pork roasts heated at different rates. The muscles were cooked in stainless-steel, perforated heating chambers at oven temperatures of 150, 200, or 250 degrees C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The results of moisture, crude fat, protein, sodium chloride, and pH analysis are listed in Table 1. Heat treatment after packaging decreased moisture content and pH values (Shin and others 1993), whereas protein and sodium chloride content increased. With the exception of the group treated at 99 °C, there were no significant differences ( P > 0.05) in the crude fat content of the other treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…The results of moisture, crude fat, protein, sodium chloride, and pH analysis are listed in Table 1. Heat treatment after packaging decreased moisture content and pH values (Shin and others 1993), whereas protein and sodium chloride content increased. With the exception of the group treated at 99 °C, there were no significant differences ( P > 0.05) in the crude fat content of the other treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, Silva et al (1993) suggested that the high water binding capacity of pre-rigor muscle resulted from a high pH and ATP content. Thus, differences in pH values between the prerigor and the post-rigor muscle could lead to the disparity in cooking shrinkage (Shin et al, 1999). As a result of the superior processing qualities of pre-rigor muscle, all samples prepared with pre-rigor muscle had a lower cooking loss.…”
Section: Ph and Colormentioning
confidence: 99%
“…Ray et al (1983) cooked beef semimembranosus and semitendinosus roasts and Loucks et al (1984) cooked beef semimembranosus roasts at 1 hr and 48 hr postmortem and found that shear values and sensory panel ratings showed that prerigor cooked roasts were less tender than postrigor cooked roasts. Shin et al (1993) cooked pork and beef roasts from triceps brachii in a conventional oven at 150, 200, or 250°C and reported that prerigor cooked roasts were less tender than postrigor cooked roasts.…”
Section: Introductionmentioning
confidence: 99%